골격성 III급 무치악 환자에서 전치부 중립대를 고려한 총의치 제작 증례 - 김수헌(Su-Hun Kim); 김형준(Hyung-Jun Kim); 박상원(Sang-Won Park); 임현필(Hyun-Pil Lim); 박찬(Chan Park); 장우형(Woo-hyung Jang) (Journal of dental rehabilitation and applied science, 2024)
In the case of skeletal class III edentulous patients, the stability of dentures can be achieved by using a crossbite by considering the residual ridge relationship when fabricating complete dentures. Forming the anterior teeth in a normal occlusal relationship in a skeletal class III ridge relationship may reduce the stability of the denture by increasing the anterior cantilever. However, when patients use complete dentures, not only functional aspects but also aesthetic aspects are important. The aesthetics of complete dentures depends on how the anterior artificial teeth are arranged, and cases of complete denture fabrication using normal occlusion or edge-to-edge bite in edentulous patients with skeletal class III ridge relationships have been reported. In this case, complete dentures were fabricated for an edentulous patient with a skeletal class III edentulous patients by forming anterior edge-to-edge bite considering neutral zone in maxillary anterior teeth, and good aesthetic and functional results were obtained. 골격성 3급 무치악 환자의 경우 총의치 제작 시 잔존치조제 관계를 고려하여 교차교합을 형성해 줌으로써 의치의 안정을 얻을 수 있다. 골격성 3급 악간관계에서 전치부를 정상교합 관계로 형성하는 것은 전방 캔틸레버를 가중시켜 의치의 안정을 저하시킬 수 있다. 하지만, 환자들은 총의치를 사용할 때 기능적인 면 뿐 아니라 심미적인 면 또한 중요시한다. 전치부 인공치들이 어떻게 배열되느냐에 따라 총의치의 심미성이 좌우되어, 골격성 3급 악간관계를 갖는 무치악 환자에서 정상교합이나 절단교합을 활용한 총의치 제작 증례가 보고되고 있다. 본 증례에서는 3급 악간관계를 갖는 무치악 환자에게 상악 전치부에 중립대를 고려하여 전치부 절단교합을 형성하여 의치를 제작하였고, 우수한 심미적, 기능적 결과를 얻었다.